Genetic variability and divergence studies for yield and its related traits in rice (Oryza sativa L.) - Singh, S. K.; Kumar, S. C. Manoj; Korada, Mounika; Khaire, Amrutlal; Majhi, Prasanta Kumar; Singh, D. K.; Jayasudha, S. (Research Trend, 2021)
The amount of genetic variability present in crop germplasm and the knowledge of its nature and magnitude is very important before starting any crop improvement program. In this view, fifty-five rice genotypes were evaluated for studying the genetic parameters (genetic variability, heritability and genetic advance as percent of mean) and genetic divergence for yield contributing characters at three different locations in Eastern Uttar Pradesh, India. The study was conducted during Kharif 2020 using Alpha lattice design. The data were collected on 15 quantitative traits. The combined ANOVA revealed the presence of significant variability in experimental material for all the traits under study across all three locations. High GCV and PCV were recorded for traits like grain yield per plot, biomass and grain yield per hectare. High heritability with high genetic advance as percent of mean was reported for plant height, number of productive tillers per plant, filled grains per panicle, grain yield per plot, grain yield per hectare, biomass, harvest index, test weight, and kernel L/B ratio. This suggests that these characters are governed by additive genes in their expression, implying that environmental influence is minimal and that they will respond better to selection. Further, genetic diversity analysis among the 55 rice genotypes using Mahalanobis’s D2 distributed them into eight clusters with cluster I containing the maximum number of genotypes. The highest intra-cluster distance was recorded in cluster VII. The maximum inter-cluster distance was observed between clusters V and VI indicating wider genetic diversity between these clusters, and hence, crosses involving parents belonging to these clusters are likely to produce wide variability and transgressive segregants with high heterotic effects.